Technology is too important to leave to technologists - Dunning , Jeremy; Waite, David; Kropp, Keith; Gantz , Thomas; Kaur, Abtar; Vidali , Ari; Hunt , Tom; Vandermolen, Larry; Rogers , Richard (2004)
The TALON/nPower learning object suite, developed by Arjuna Multimedia, is a set of 39 repurposeable learning object templates based on styles of teaching and learning that are designed to allow instructors and designers to create substantive learning objects without changing any of the source code. The instructor or designer can use the templates to design a new learning object without writing or changing any source code. The templates are simple enough that instructors with little or no programming experience can create their own learning objects. This paper examines the experiences of two professors’ use of the templates to create interactive exercises for their courses.